POLA PERILAKU KONSUMSI MAHASISWA MUSLIM (Studi Kasus Mahasiswa FEBI IAIN Kendari 2018-2021) - Ririn Indah Zulfiah; Sitti Nur Annisa Amalia (AL-KHARAJ, 2022)
AbstractThe pattern of consumption behavior is a person's lifestyle, especially among young people or students today who cannot be separated from technology and modern flows according to the times. Based on this, the researcher was interested and wanted to know the pattern of consumption behavior of students at the Faculty of Economics and Islamic Business IAIN Kendari, especially in the Islamic Economics study program class 2018 - 2021 in the perspective of Islamic economics and the use of their income (pocket money) to carry out consumption activities, especially on non-food consumption.This study aims to determine the pattern of non-food consumption behavior in students at the Faculty of Economics and Islamic Business IAIN Kendari, especially in the Islamic Economics study program class 2018 - 2021 as well as in the perspective of Islamic economics and to find out students in using their income (pocket money) to carry out consumption activitie , especially in non-food consumption.This study uses a quantitative descriptive analysis method that does not use hypothesis testing but is an attempt to answer the researcher's questions so that it is hoped that an overall picture of a real phenomenon will emerge and explain or describe the variables in this study. This research was conducted by giving questionnaires and giving interviews which are related to the variables of consumption behavior patterns of Muslim students.The results of this study are (1) students at the Faculty of Islamic Economics and Business IAIN Kendari, especially in the Islamic Economics study program class 2018 - 2021, in the pattern of non-food consumption behavior, most of them are said to be relatively the same and have diverse needs between male and female students woman. (2) Students at the Islamic Economics and Business Faculty, IAIN Kendari, especially in the Islamic Economics study program class 2018 - 2021, show that students from an Islamic economic perspective, their consumption behavior patterns are still said to be not in accordance with what has been shari'ah according to Islamic teachings. (3) Students at the Faculty of Islamic Economics and Business, IAIN Kendari, especially in the Islamic Economics study program class 2018 - 2021, show that in using income (pocket money), students are more likely to allocate it to fulfilling needs beyond limits and prioritize needs that are actually less needed not even useful and can be postponed, especially in the needs of entertainment, care/cosmetic, and especially in tobacco/cigarettes.AbstrakPola perilaku konsumsi merupakan gaya hidup seseorang, terutama di kalangan anak muda atau pelajar saat ini yang tidak lepas dari teknologi dan arus modern sesuai dengan perkembangan zaman. Berdasarkan hal tersebut, peneliti tertarik dalam membahas bagaimana pola perilaku konsumsi mahasiswa fakultas Ekonomi dan Bisnis Islam IAIN Kendari, khususnya pada program studi Ekonomi Islam angkatan 2018 – 2021 dalam perspektif ekonomi Islam dan penggunaan pendapatannya (uang jajan) untuk melakukan kegiatan konsumsi,  terutama pada konsumsi non-makanan.Penelitian ini bertujuan untuk mengetahui pola perilaku konsumsi non pangan pada mahasiswa Fakultas Ekonomi dan Bisnis Islam IAIN Kendari, khususnya pada program studi Ekonomi Islam angkatan 2018 – 2021 serta dalam perspektif ekonomi Islam dan untuk mengetahui mahasiswa dalam menggunakan pendapatannya (uang jajan) untuk melakukan kegiatan konsumsi,  terutama dalam konsumsi non-makanan.Penelitian ini menggunakan metode analisis deskriptif kuantitatif yang tidak menggunakan pengujian hipotesis tetapi merupakan upaya untuk menjawab pertanyaan peneliti sehingga diharapkan akan muncul gambaran keseluruhan dari suatu fenomena nyata dan menjelaskan atau mendeskripsikan variabel-variabel dalam penelitian ini. Penelitian ini dilakukan dengan memberikan kuesioner dan memberikan wawancara yang berkaitan dengan variabel pola perilaku konsumsi mahasiswa muslim.Penelitian ini menghasilkan, bahwa (1) Mahasiswa Fakultas Ekonomi dan Bisnis Islam IAIN Kendari angkatan 2018 – 2021, dalam pola perilaku konsumsi non pangan, kebanyakan dari mereka dikatakan relatif sama dan memiliki kebutuhan yang beragam antara mahasiswa laki-laki dan perempuan perempuan. 2) Mahasiswa Fakultas Ekonomi dan Bisnis Islam, IAIN Kendari angkatan 2018 – 2021, menunjukkan bahwa mahasiswa dari perspektif ekonomi Islam, pola perilaku konsumsinya masih dikatakan tidak sesuai dengan apa yang telah menjadi syari'ah menurut ajaran Islam. (3) Mahasiswa Fakultas Ekonomi dan Bisnis Islam, IAIN Kendari angkatan 2018 – 2021, menunjukkan bahwa dalam menggunakan pendapatan (uang saku), mahasiswa lebih cenderung mengalokasikannya untuk memenuhi kebutuhan di luar batas dan mengedepankan kebutuhan yang sebenarnya kurang dibutuhkan bahkan tidak berguna dan dapat ditunda,  terutama dalam kebutuhan hiburan, perawatan/kosmetik, dan khususnya pada tembakau/rokok.